Biotic effects dominate the inter-annual variability in ecosystem carbon exchange in a Tibetan alpine meadow. (12th January 2022) - Xu, Mingjie; Sun, Yi; Zhang, Tao; Zhang, Yangjian; Zhu, Juntao; He, Yongtao; Wang, Liwei; Yu, Guirui
Abstract: The alpine meadow ecosystem in Tibet is fragile and sensitive, and its carbon sink function with respect to climate change has become a matter of widespread concern. Therefore, this study aims to clarify the inter-annual variations (IAVs) in the carbon fluxes in an alpine meadow and to further quantify the contributions of the driving factors to the IAVs. Based on 7 years of flux data (2012–2018) and the corresponding climatic and biotic data, a set of look-up tables was used to separate and quantify the IAV sources. Furthermore, linear perturbation analyses were employed to quantify the contributions of each key factor. During 2012–2018, the net ecosystem productivity (NEP), gross primary productivity (GPP) and ecosystem respiration (Re) of this alpine meadow were 3.31 ± 26.90, 210.18 ± 48.35 and 206.88 ± 28.45 g C m −2 y −1, respectively, which indicated relatively large IAVs. When the contributions of climatic and biotic effects were distinguished and quantified, the dominant effects of biotic factors emerged. Additionally, negative interactions between climatic and biotic effects were detected. Among the climatic factors, only soil water content contributed relatively more to the IAVs and played a role in regulating the interactions between climatic and biotic effects. These results suggest that biotic effects must be carefully considered to reduce the uncertainties associated with future carbon flux estimates.